METACOGNITIVE STRATEGY IN INDIRECT LEARNING STRATEGIES USED BY EFL STUDENTS IN ACADEMIC SPEAKING CLASS OF ENGLISH DEPARTMENT SURABAYA STATE UNIVERSITY (RETAIN, 2015)
Abstrak Penelitian ini bertujuan untuk mengetahui bagaimana metakognitif strategi dalam indirect learning strategies digunakan oleh siswa dalam kelas academic speaking di program Pendidikan Bahasa Inggris dari Universitas Negeri Surabaya dan bagaimana penampilan berbicara mereka setelah menggunakan metakognitif strategi. Dalam hal ini, metakognitif strategi diambil berdasarkan teori dari Oxford (1990). Dia mengatakan bahwa strategi ini memiliki tiga strategi utama; centering, arranging & planning and evaluating the learning. Selain itu, data-data dikumpulkan melalui observasi, wawancara dan speaking rubrik. Penelitian ini merupakan penelitian kualitatif sehingga hasilnya akan digambarkan melalui kata-kata. Peneliti mengambil semua siswa dalam kelas F academic speaking. Peneliti juga fokus pada enam siswa sebagai perwakilan subjek dalam penelitian ini. Hal ini dikarenakan penelitian kualitatif harus menganalisis subjek secara mendalam. Hasil pertama dari penelitian ini menunjukkan bahwa siswa menggunakan metakognitif strategi dengan berbagai cara. Kebanyakan siswa selalu menggunakan tiga strategi utama dari metakognitif strategi seperti centering, arranging & planning and evaluating the learning dalam proses pembelajaran mereka untuk dapat menyelesaikan tugas-tugas secara maksimal. Dalam hal ini, siswa melakukan paid attention and delayed speeches dalam centering the learning. Kemudian mereka melakukan found out, planned dan seeking practice opportunities dalam arranging & planning the learning. Terakhir, siswa melakukan self monitoring dan self evaluating dalam evaluating the learning. Dengan menggunakan metakognitif strategi, siswa dapat lebih mudah untuk menyampaikan presentasi dan menguasai materi dengan baik. Strategi ini membantu siswa meningkatkan kepercayaan diri. Hasil kedua menunjukkan bahwa penampilan berbicara siswa menunjukkan hasil yang memuaskan setelah menggunakan strategi ini dalam academic speaking. Kebanyakan siswa sudah memenuhi kriteria untuk sebuah penampilan berbicara yang baik. Kesimpulannya, penggunaan metakognitif strategi dapat membantu meningkatkan kemampuan berbicara siswa dalam menyampaikan presentasi. Kata Kunci: Metacognitive learning strategies, academic speaking, centering the learningarranging and planning the learning, evaluating the learning. Abstract This study was conducted to know how metacognitive strategy in indirect learning strategies were used by the students in academic speaking class of English Education study program in State University of Surabaya and their speaking performances after using metacognitive strategies. In this case, the metacognitive learning strategies are based on the theory from Oxford (1990). She states that the strategies have three main strategies; centering, arranging & planning and evaluating the learning. Moreover, the data were collected through observation, interview and speaking rubric. This study was conducted qualitatively so that the result would be described in the form of words. The researcher only took all students from academic speaking class, specifically in Class F. The researcher involved six students with different scores in the previous midterm test as the subjects of the study since descriptive qualitative research and the use of this strategy should be analysed in personally or in in-depth analysis. The first result of the study revealed that the students used metacognitive learning strategies in many ways. Most of the students always used three main sets of metacognitive strategies such as centering, arranging & planning and evaluating the learning in their learning process to accomplish the task In this case, the students paid attention and delayed speeches in centering the learning. Moreover, they also found out, planned and sought practice opportunities in arranging and planning the learning. The last, three students did self monitoring and self evaluating in evaluating the learning, but one student did not evaluate the learning. By using metacognitive strategies, the students got it easier to deliver presentations and master the material well. Moreover, this strategy could enhance the students’ self confidence. While the second result showed that the students’ speaking performances were good after using metacognitive learning strategies in academic speaking. Most of them had already fulfilled the criteria of a good speaking perfomance. In short, the use of metacognitive learning strategies could help enhance the students’ speaking ability in delivering presentations. Key Words: Metacognitive learning strategies, academic speaking, centering the learningarranging and planning the learning, evaluating the learning.